Influence of CaO and CuO on Barium Zinc Tantalate (BZT) Dielectric Properties (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
The structure and dielectric properties of Barium Zinc Tantalate (BZT) doped by copper oxide (CuO) and calcium oxide (CaO) with a variety of values of mol% doping from 0, 0.1, 0.25, 0.5, 1.0, 1.5 and 2.5 were prepared using a solid state method. A small amount of doping elements increased the relative density. The dielectric constant (?r) value of the BZT significantly improved with the addition of the CuO and CaO for the specimens sintered at 1250°C and it could be explained by the increase of the relative density. The tan ? of the CuO and CaO doped with BZT ceramics is lower than pure BZT ceramics, and decreases as the CuO and CaO content increases. Minimum return loss (dB) shown that the best results are produced when it is doped with 0.25 mol% CaO and 0.5 mol% for CuO sintered at 1250°C.
Keywords: barium zinc tantalate; copper oxide; calcium oxide; relative density; dielectric properties